Evaluating the triglyceride-glucose index as a biomarker for inflammatory bowel disease risk: insights from a UK Biobank prospective study - Zhang, Manli; Hu, Feng; Miao, Ling; Li, Fan; Rao, Min (Frontiers in Immunology, 2025)
BackgroundInflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn’s disease (CD), is a chronic inflammatory condition with rising global incidence. This study examines the association between the triglyceride-glucose (TyG) index, a marker of insulin resistance, and both the risk and prognosis of IBD.MethodsThis study analyzed data from 327,089 participants in the UK Biobank. The TyG index was calculated based on fasting triglyceride and glucose levels, and participants were categorized into quartiles. Cox proportional hazards models, restricted cubic splines (RCS), subgroup analyses, and mediation analyses were employed to explore the association between TyG and the risk of UC and CD. Covariates were adjusted for age, sex, race, socioeconomic and lifestyle factors, physical activity, common chronic diseases, and polygenic risk scores. Multiple sensitivity analyses were conducted to ensure the robustness of the results.ResultsAn elevated TyG index was significantly associated with an increased risk of IBD. For each unit increase in TyG, the risk of UC increased by 14.3% (HR: 1.143, 95% CI: 1.053–1.241), while the risk of CD increased by 13.8% (HR: 1.138, 95% CI: 1.006–1.286). Participants in the highest TyG quartile had a 28.0% higher risk of CD (HR: 1.280, 95% CI: 1.050–1.560) and a 17.8% higher risk of UC (HR: 1.178, 95% CI: 1.028–1.351) compared to those in the lowest quartile. Mediation analysis revealed that the association between TyG and the incidence of CD and UC was mediated by multiple factors, including white blood cell count, mean corpuscular hemoglobin, C-reactive protein, total bilirubin, neutrophil count, reticulocyte percentage, and high-light scatter reticulocyte percentage. The proportion of mediation effects ranged from 1.44% to 30.97%.ConclusionThis study is the first to systematically investigate the relationship between the TyG index and both the risk and prognosis of IBD, using a large cohort from the UK Biobank. The findings reveal a significant positive association between the TyG index and the risk of developing UC and CD, suggesting that a higher TyG index may serve as an independent predictor of IBD risk.